2022
DOI: 10.2478/ngoe-2022-0009
|View full text |Cite
|
Sign up to set email alerts
|

Board Structure and Bank Performance: The Mediating Role of Intellectual Capital

Abstract: Intellectual capital in the knowledge era is a strategic advantage of board structure, which leads to the improvement of a company’s work and the achievement of its goals. The aim of this study is to develop a structural model that connects the corporate governance, intellectual capital and financial performance of the banking sector. Corporate governance is conceptualised by the board of directors as the main internal mechanism of corporate governance, which is measured by the size of the board of directors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 64 publications
2
8
0
Order By: Relevance
“…Previous studies, including those conducted by Babić et al [9] and Simić [84], have generally found that the size of the board of directors does not have a statistically significant impact on the profitability of banks in Serbia. However, Nikolić et al [44] found that board size has no significant effect on bank profitability as measured by ROA, but does have a negative impact on profitability as measured by ROE. Based on the above, the first research hypothesis was defined: H 1 .…”
Section: Review Of Literature and Definition Of Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies, including those conducted by Babić et al [9] and Simić [84], have generally found that the size of the board of directors does not have a statistically significant impact on the profitability of banks in Serbia. However, Nikolić et al [44] found that board size has no significant effect on bank profitability as measured by ROA, but does have a negative impact on profitability as measured by ROE. Based on the above, the first research hypothesis was defined: H 1 .…”
Section: Review Of Literature and Definition Of Hypothesesmentioning
confidence: 99%
“…According to this view, it is considered that women, unlike men, have a higher level of education and other skills and thus positively influence the efficiency of the board and the performance of the company [62]. Greater diversity enables new views of the environment, richer sources of information, and increased creativity and innovation [7,44,62,63,80]. This is supported by the fact that female members of management boards attend meetings more often than their colleagues and are more actively involved in them [26].…”
Section: Review Of Literature and Definition Of Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Corporate governance regulates relationships between related parties such as management, shareholders, board of commissioners and other stakeholders (El-Chaarani, Abraham, & Skaf, 2022). The regulation of the relationship between the parties involved will be related to their rights and obligations and will give rise to an agency theory where management of the banking sector will be separate from ownership (Nikolić, Nielsen, & Peković, 2022). Separating management from ownership will create a conflict of interest between banking owners and banking administrators such as management or directors (Al-Janadi, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sample selection procedure CEE it is CEE coefficient of bank i at time t; VA it represents total VA produced by bank i at time t; CE it is CE (book value of net assets) of bank i at time t, CE it is CE measured as the book value of total assets minus total liability[7,82,152,207,218,219].The VAIC is calculated in the fifth stage to illustrate how much new value has been created per monetary unit invested in each resource.where VAIC it , the VA intellectual coefficient for the bank i at time t; CEE it , VA by CE coefficient for bank i at time t; HCE it , the HCE for bank i at time t; SCE it , SC VA for bank i at time t.On the sixth stage, relational capital efficiency is calculated to show how relational capital (a bank's ability to create relationships with customers, suppliers, and other external stakeholders) contributes to value creation[137,191,208,213].where RCE it is RC coefficient of bank i at time t; VA it represents total VA produced by bank i at time t; RC it is RC of bank i at time t, RC it is RC measured as the marketing and advertisement expenses[29,69,136,207,218,227].VAIC it = HCE it + SCE it + CEE it VAIC it ,the VA intellectual coefficient for the bank i at time t; CEE it , VA by CE coefficient for bank i at time t; HCE it , the HCE for bank i at time t; SCE it , VA by SC for bank i at time t. Being the Pulic model, the value-added intellectual capital coefficient (VAIC) is divided into three major components: SCE, HCE, and CEE…”
mentioning
confidence: 99%